When Experience Meets Description: How Dyads Integrate Experiential and Descriptive Information in Risky Decisions - Lejarraga, Tomás; Müller-Trede, Johannes (Management Science, 2017)
How do teams make joint decisions under risk when some team members learn about a prospect from description and others learn from experience? In a series of experiments, we find that two-person teams composed of one participant who learns from description and a second participant who learns from experience arrive at shared decisions via mutual concessions. In doing so, they attenuate individual biases, such as the overweighting and underweighting of the probability of rare events. The social interaction thus leads dyads to make shared decisions that follow normative standards more closely than the decisions made by individual decision makers. Finally, in processing experiential information, dyads appear to be sensitive to the reliability of the experience: the more reliable the experiential information, the larger its influence on the dyad’s decision. Data, as supplemental material, are available at http://dx.doi.org/10.1287/mnsc.2016.2428 . This paper was accepted by Teck-Hua Ho, judgment and decision making.